Penguatan Peran Masyarakat dalam Pemantauan Lingkungan Bangunan Pengendali Banjir PLTS Isimu di Desa Molowahu, Kabupaten Gorontalo - Anton Kaharu; Faiza A. Dali; Satar Saman; Muhammad Rizal Mahanggi; Berni Idji; Mohamad Faisal Dunggio (Yayasan Daarul Huda Kruengmane, 2026)
The construction of flood control structures in the area of the Isimu Solar Power Plant (PLTS Isimu) in Molowahu Village, Gorontalo Regency, requires continuous environmental monitoring to ensure the sustainability of the structures and to minimize environmental impacts on surrounding communities. However, community involvement in environmental monitoring around the project area remains limited, highlighting the need to strengthen the role of local communities through participatory-based approaches. This Community Service Program aims to enhance community knowledge, awareness, and capacity in conducting environmental monitoring around the flood control structures of PLTS Isimu. The program was implemented through socialization activities, environmental education, participatory discussions, and community assistance in understanding simple environmental monitoring indicators, including water flow conditions, sedimentation, and environmental cleanliness. The target beneficiaries were residents living in the vicinity of the flood control structures in Molowahu Village. The results indicate an improvement in community understanding and awareness of the importance of environmental monitoring, as well as increased community participation in maintaining the function of flood control structures and the surrounding environment. This program is expected to support sustainable environmental management and strengthen collaboration among communities, village authorities, and relevant stakeholders in flood mitigation efforts in Molowahu Village, Gorontalo Regency.